A comparative study on the prevalence of microcytic anemia and associated age of anemic patients from Benghazi city - Tarek A. Guseibat , Mona M. said (Journal of Pure & Applied Sciences, 2020)
Anemia is a public health problem marked by deficiency of RBCs and classified on the basis of size into microcytic, normocytic and macrocytic anemia. This study aimed to determine the prevalence of  microcytic anemia with the other types of anemia and related age groups in Benghazi city. there have been very few studies describing the prevalence of anemia types. A cross sectional study was performed in duration of 6 months, a total of 299 cases were studied, blood samples were collected and hematologicaly tested for CBC in hematology cell counter .As a result(72.9%) of the total anemic patients were females and (27.09%) were males, prevalence of microcytic anemia was the highest (59.19%) among anemia types, the most infected age group in females was (21-40 years) and in males was (1-10 years). Regarding normocytic anemia, the prevalence was (39.46%) and age groups (21-40 years) and (>40 years) were the most infected in both females and males respectively. Prevalence of macrocytic anemia was the lowest (1.33%), (75%) of infected cases were in age group (>40 years) and (25%) were in (21-40 years) age group. According to this study females are more anemic than males , microcytic anemia is the most predominant type of anemia followed by normocytic anemia and finally macrocytic anemia is the lowest prevalent type of anemia. More studies are needed to determine the main causes of prevalence each type of anemia.